Life-space intervention: implications for caregiving - Kiaras Gharabaghi; Carol Stuart (Scottish Journal of Residential Child Care)
This article explores the concept of life-space intervention, and proposes four dimensions of a single, unified life-space: The physical dimension, where young people's lives unfold; the mental dimension, reflecting how young people make sense of their life-space; the relational dimension, assigning 'space' to young people's relationships; and, the virtual dimension, constituted by technology-based platforms for the construction of identity as well as by the imagination and fantasies held by young people. The implications of this conceptualization of a multi-dimensional single life-spaced are discussed in relation to being present with young people, and the agency-structure dilemma is explored in relation to generating change in the lives of young people.